An angle type electric double-wall corrugated pipe and a method for manufacturing the same

CN121716370BActive Publication Date: 2026-10-27ZHEJIANG HOSHARE IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610085912.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-22
Publication Date
2026-10-27
Estimated Expiration
2046-01-22

AI Technical Summary

Technical Problem

[0004]本申请提供了一种角型电力双壁波纹管及其制备方法,旨在解决现有角型电力双壁波纹管因高填充改性导致刚性高而韧性差、易在施工中压溃开裂的技术问题

Benefits of technology

本申请通过在管材外壁中引入金属酞菁包覆炭黑、不饱和烃类弹性体、马来酸酐接枝聚烯烃及含咪唑链段的改性尼龙,实现了聚丙烯管材的刚韧平衡。其中,炭黑提供基础刚性,金属酞菁包覆层抑制其与聚合物基体的化学交联,保障韧性;丁苯橡胶通过接枝与π-π作用实现增韧与填料分散;改性尼龙则借助咪唑-金属酞菁配位形成非刚性的配位网络,同步提升环刚度与抗冲击性。最终,在维持环刚度的前提下,显著改善了角型波纹管在切割、搬运及安装过程中的结构稳定性,有效避免波纹压溃与脆性断裂,满足地下电力保护管对高刚性与高韧性的需求。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of angle type electric power double-wall corrugated pipe and its preparation method.The inner wall of the corrugated pipe includes the following mass parts of raw materials: polypropylene 100 parts, filler 10-20 parts, lubricant 1-3 parts;The outer wall of the corrugated pipe includes the following mass parts of raw materials: polypropylene 100 parts, unsaturated carbon chain rubber 5-10 parts, maleic anhydride grafted polyolefin 3-6 parts, modified carbon black 15-25 parts, free radical initiator 0.03-0.05 parts, lubricant 1-3 parts;The surface of the modified carbon black is coated with a layer of metal phthalocyanine molecules.The application aims to solve the technical problems of the existing angle type electric power double-wall corrugated pipe, which has high rigidity and poor toughness due to high filling modification, and is prone to crushing and cracking during construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polypropylene materials, and in particular to an angled double-walled corrugated pipe for electric applications and its preparation method. Background Technology

[0002] With the rapid development of urban underground pipe network construction, the performance requirements for power cable protection pipes, as a key infrastructure to ensure power transmission safety, are becoming increasingly stringent. Among them, angled double-wall corrugated power pipes have been widely used in municipal power engineering due to their unique structural design. Specifically, their smooth inner wall facilitates cable threading, while the regular corrugated outer wall enhances circumferential stiffness. Furthermore, their right-angled or near-right-angled cross-section allows for close fitting into cable wells or trench corners, effectively saving space and simplifying construction layout.

[0003] Currently, these corrugated pipes are mostly made of polypropylene (PP) based materials through a double-layer co-extrusion and corrugated molding process. To meet the requirements of underground burial conditions for withstanding soil loads and traffic dynamic loads, a large amount of inorganic reinforcing fillers (such as talc, calcium carbonate, glass fiber, etc.) are usually introduced into the polypropylene matrix, or highly crystalline homopolymer PP is used to significantly improve the ring stiffness and compressive strength of the pipe. However, this material modification strategy oriented towards rigidity enhancement often leads to increased brittleness of the system and a significant decrease in impact toughness. In actual construction, especially during on-site cutting, handling, or localized stress, the corrugated structure of the pipe is prone to crushing, cracking, or even brittle fracture, which not only affects installation efficiency but may also damage its structural integrity and weaken its long-term service performance. More significantly, due to the stress concentration at the corners of the angled structure, coupled with the limited ductility of highly filled modified PP, this area is more prone to failure under mechanical processing or external impact. Therefore, how to effectively improve the impact toughness of angular double-wall corrugated power pipes while maintaining sufficient ring stiffness to ensure compressive strength and avoid construction damage has become a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0004] This application provides a angular double-wall corrugated pipe for power transmission and its preparation method, aiming to solve the technical problem that existing angular double-wall corrugated pipes for power transmission have high rigidity but poor toughness due to high filler modification, and are prone to crushing and cracking during construction.

[0005] In a first aspect, this application provides an angled double-walled corrugated pipe for electric power, wherein the inner wall of the corrugated pipe comprises the following raw materials in parts by weight: 100 parts of polypropylene, 10-20 parts of filler, and 1-3 parts of lubricant. The outer wall of the corrugated pipe comprises the following raw materials in parts by weight: 100 parts polypropylene, 5-10 parts unsaturated hydrocarbon elastomer, 3-6 parts maleic anhydride grafted polyolefin, 15-25 parts modified carbon black, 0.03-0.05 parts free radical initiator, and 1-3 parts lubricant; the modified carbon black is coated with a metal phthalocyanine molecular layer.

[0006] In any of the above technical solutions, the melt flow rate of the polypropylene is 0.1 to 1.0 g / 10 min.

[0007] In any of the above technical solutions, the preparation method of the modified carbon black is as follows: Carbon black was dispersed in an organic solvent at a concentration of 10–30 mg / mL, and then sonicated to obtain a suspension. A phthalonitrile precursor with a molar ratio of 4 to 7:1 was mixed with a metal salt and added to a suspension, so that the total mass ratio of the phthalonitrile precursor to the metal salt to the carbon black was 4 to 10:1. The mixture was stirred and reacted at 170 to 230°C for 2 to 5 hours under an inert atmosphere. After the reaction was completed, the mixture was cooled, filtered, washed, and dried to obtain carbon black with a metal phthalocyanine molecular layer on its surface.

[0008] In any of the above technical solutions, the organic solvent is selected from N-methylpyrrolidone or trichlorobenzene.

[0009] In any of the above technical solutions, the drying is performed under vacuum at 60–90°C for 8–24 hours. In any of the above technical solutions, the average particle size of the carbon black is 20-100 nm.

[0010] In any of the above technical solutions, the metal salt is a zinc salt hydrate or a copper salt hydrate.

[0011] This application significantly improves the rigidity and dimensional stability of the polypropylene matrix by introducing a large amount of modified carbon black into the outer wall raw material, thereby effectively ensuring the high ring stiffness and compressive strength of the angled double-wall corrugated pipe under underground burial conditions. At the same time, unsaturated hydrocarbon elastomers are added to the system as toughening phases, and in conjunction with free radical initiators, the double bonds in the rubber are promoted to undergo grafting reactions with the polypropylene main chain during the extrusion process to form an "island" structure, which improves the impact toughness of the material and effectively inhibits the crushing or brittle fracture of the corrugated structure due to local stress during construction.

[0012] However, conventional carbon black surfaces are rich in active defect sites and oxygen-containing groups, making them highly susceptible to grafting with polypropylene or rubber under free radical conditions, forming rigid cross-linked interfaces that exacerbate brittleness. Therefore, this application employs in-situ synthesis and other methods to coat the carbon black surface with a layer of metal phthalocyanine molecules. This coating not only shields the active sites on the carbon black surface, blocking its direct reaction pathway with free radicals and preventing the formation of rigid cross-links, but also retains the physical reinforcing effect of carbon black, thereby achieving a balance between stiffness and toughness in the pipe while maintaining high ring stiffness.

[0013] In any of the above technical solutions, the raw material of the outer wall includes 5 to 12 parts of modified nylon, wherein the molecule of the modified nylon contains an imidazole segment.

[0014] In any of the above technical solutions, the modified nylon is obtained by polycondensation of a dicarboxylic acid, an imidazole-containing dicarboxylic acid, and a diamine in a molar ratio of 1:0.05-0.15:1.1-1.3.

[0015] In any of the above technical solutions, the imidazole dicarboxylic acid is 4,5-imidazole dicarboxylic acid.

[0016] In any of the above technical solutions, the dicarboxylic acid is adipic acid and the diamine is hexamethylenediamine.

[0017] To further enhance the rigidity-toughness balance of the pipe material, this application introduces a modified nylon containing imidazole segments into the outer wall raw material. This nylon is prepared by co-condensation of adipic acid, 4,5-imidazolium dicarboxylic acid, and hexamethylenediamine. The imidazole ring embedded in its molecular chain possesses lone pairs of electrons, which can coordinate with the metal phthalocyanine coated on the carbon black surface. Since zinc / copper phthalocyanine retains open coordination sites in the axial direction, it can construct dynamically reversible coordination bonds with the nitrogen atoms of the imidazole, thereby constructing a non-covalent but strongly interacting coordination network between the carbon black and the polymer matrix. This network provides additional structural support under static loads, improving ring stiffness; under impact, the coordination bonds preferentially break and dissipate energy, thus significantly enhancing the material's impact resistance. Furthermore, the terminal amine groups of the modified nylon can react with maleic anhydride-grafted polyolefins in the system, improving its compatibility in the polypropylene matrix and achieving uniform dispersion of the nylon phase in the polypropylene phase.

[0018] In any of the above technical solutions, the unsaturated hydrocarbon elastomer is butyl rubber, propylene butadiene rubber, or styrene-butadiene rubber, preferably styrene-butadiene rubber.

[0019] This application selects styrene-butadiene rubber (SBR) as a toughening agent. Besides its excellent elasticity and grafting activity, SBR's molecular chain contains a benzene ring structure, which allows it to interact π-π with the conjugated planes of the metal phthalocyanine coating on the carbon black surface. This non-covalent interaction helps guide the modified carbon black to disperse more uniformly in the polypropylene melt, reducing stress concentration points caused by agglomeration. The uniformly distributed carbon black particles not only improve the reinforcing efficiency but also synergistically form a toughening structure with SBR. The rubber phase absorbs impact energy, while the well-dispersed carbon black inhibits crack propagation. Thus, the π-π interaction indirectly promotes the synergy between the rigid filler and the elastomer, further enhancing the overall impact toughness of the pipe.

[0020] Secondly, this application provides a method for manufacturing a angular double-walled corrugated power pipe, comprising: The corrugated pipe raw materials described in any one of the first aspects are mixed according to the formula, and the mixed material is dried and preheated. The dried and preheated materials are fed into a twin-screw co-extrusion system for plasticizing and extrusion to form a concentric double-layer tube blank. The tube blank enters a corrugated forming machine, where it is molded, cooled and shaped, and cut to a fixed length to obtain a double-wall corrugated pipe.

[0021] In any of the above technical solutions, the drying preheating temperature is 60-80℃, and the drying time is 2-4 hours.

[0022] In summary, this application has the following beneficial effects: This application achieves a balance between rigidity and toughness in polypropylene pipes by introducing metal phthalocyanine-coated carbon black, unsaturated hydrocarbon elastomers, maleic anhydride-grafted polyolefins, and modified nylon containing imidazole segments into the outer wall of the pipe. Carbon black provides basic rigidity, while the metal phthalocyanine coating inhibits chemical cross-linking between carbon black and the polymer matrix, ensuring toughness. Styrene-butadiene rubber achieves toughening and filler dispersion through grafting and π-π interactions. The modified nylon, through imidazole-metal phthalocyanine coordination, forms a non-rigid coordination network, simultaneously improving ring stiffness and impact resistance. Ultimately, while maintaining ring stiffness, the structural stability of the angled corrugated pipe is significantly improved during cutting, handling, and installation, effectively preventing corrugation crushing and brittle fracture, thus meeting the high rigidity and high toughness requirements of underground power protection pipes. Detailed Implementation

[0023] Preparation Example Preparation Example 1-1, modified carbon black, the preparation steps are as follows: 100 g of carbon black with an average particle size of 50 nm was added to 5 L of N-methylpyrrolidone to form a suspension of 20 mg / mL. The suspension was ultrasonically dispersed at 400 W for 30 minutes to obtain a uniform black suspension. Subsequently, 500 g of phthalonitrile and 150 g of Zn(OAc)2·2H2O were ground and mixed, and then slowly added to the above suspension. The mixture was stirred for 15 minutes to ensure uniform wetting. The mixture was transferred to a three-necked reactor, and the air was replaced three times with high-purity nitrogen. The mixture was then reacted at 200 °C and 300 rpm under mechanical stirring for 3.5 hours. After the reaction was completed, the mixture was cooled to 60 °C, and the solid was collected by filtration. The solid was washed three times with hot anhydrous ethanol at 60 °C and then rinsed twice with acetone until the filtrate was colorless. Finally, the product was placed in a vacuum oven and dried at 80 °C for 16 hours to obtain modified carbon black with a zinc phthalocyanine molecular layer on the surface.

[0024] Preparation Examples 1-2, modified carbon black, the preparation steps are as follows: 100 g of carbon black with an average particle size of 80 nm was added to 6.6 L of N-methylpyrrolidone to form a suspension of 15 mg / mL. The suspension was ultrasonically dispersed at 300 W for 30 minutes to obtain a uniform black suspension. Subsequently, 320 g of phthalonitrile and 130 g of Cu(OAc)2·2H2O were ground and mixed, and then slowly added to the above suspension. The mixture was stirred for 15 minutes to ensure uniform wetting. The mixture was transferred to a three-necked reactor, and the air was replaced three times with high-purity nitrogen. The mixture was then reacted at 175 °C and 300 rpm under mechanical stirring for 2.5 hours. After the reaction was completed, the mixture was cooled to 60 °C, and the solid was collected by filtration. The solid was washed three times with hot anhydrous ethanol at 50 °C and then rinsed twice with acetone until the filtrate was colorless. Finally, the product was placed in a vacuum oven and dried at 60 °C for 20 hours to obtain modified carbon black with a copper phthalocyanine molecular layer on the surface.

[0025] Preparation Examples 1-3, modified carbon black, the preparation steps are as follows: 100 g of carbon black with an average particle size of 30 nm was added to 3.6 L of N-methylpyrrolidone to form a suspension of 28 mg / mL. The suspension was ultrasonically dispersed at 400 W for 35 minutes to obtain a uniform black suspension. Subsequently, 500 g of phthalonitrile and 150 g of Zn(OAc)2·2H2O were ground and mixed, and then slowly added to the above suspension. The mixture was stirred for 15 minutes to ensure uniform wetting. The mixture was transferred to a three-necked reactor, and the air was replaced three times with high-purity nitrogen. The mixture was then reacted at 220 °C and 300 rpm under mechanical stirring for 4.5 hours. After the reaction was completed, the mixture was cooled to 60 °C, and the solid was collected by filtration. The solid was washed three times with hot anhydrous ethanol at 60 °C and then rinsed twice with acetone until the filtrate was colorless. Finally, the product was placed in a vacuum oven and dried at 90 °C for 10 hours to obtain modified carbon black with a zinc phthalocyanine molecular layer on the surface.

[0026] Preparation Examples 1-4, modified carbon black, the preparation steps are as follows: 100 g of carbon black with an average particle size of 30 nm was added to 1.5 L of N,N-dimethylformamide. The mixture was ultrasonically dispersed at room temperature for 2 hours to form a uniform black suspension. Then, 3.5 g of zinc phthalocyanine (average particle size 20 nm) was added, and the mixture was heated to 120 °C and refluxed under a nitrogen atmosphere for 8 hours to allow the zinc phthalocyanine to adsorb onto the carbon black surface. After the reaction was complete, the mixture was cooled to room temperature, filtered, and washed twice each with 500 mL of N,N-dimethylformamide and 300 mL of anhydrous ethanol. The mixture was then dried in a vacuum oven at 80 °C for 12 hours to obtain the modified carbon black.

[0027] Preparation Examples 1-5, modified carbon black, were prepared according to the following operations: 100 g of carbon black with an average particle size of 30 nm was added to 300 mL of anhydrous ethanol, 15 mL of water, and 5 mL of vinyltrimethoxysilane. The mixture was heated to 110 °C and refluxed for 6 hours to allow the silane to hydrolyze and condense onto the carbon black surface. After the reaction was complete, the mixture was cooled, filtered, washed twice with 200 mL of ethanol, and dried under vacuum at 60 °C for 10 hours to obtain modified carbon black.

[0028] Preparation Example 2-1, modified nylon, was prepared according to the following operation: Under nitrogen protection, 5.0 mol adipic acid (730 g), 0.5 mol 4,5-imidazolium dicarboxylic acid (83 g), and 5.9 mol hexamethylenediamine (602 g) were added to a high-pressure polymerization reactor, along with 4.0 g phosphoric acid as a catalyst. The reactor was heated to 80-90 °C with stirring and held for 30 minutes to allow the adipic acid, imidazolium dicarboxylic acid, and hexamethylenediamine to fully react and form a modified nylon salt aqueous solution. The temperature was then raised to 180 °C and held at atmospheric pressure for 2 hours for pre-polymerization, during which the generated water was continuously drained and the reactor pressure was controlled to ≤0.3 MPa. The temperature was then raised to 240 °C, and the vacuum was gradually reduced to ≤100 Pa. The polymerization reaction continued for 2.5 hours until the melt viscosity stabilized. Heating was stopped, and nitrogen gas (0.2 MPa) was introduced to break the vacuum. The material was discharged, water-cooled and pelletized, and then vacuum-dried at 80 °C for 8 hours to obtain modified nylon 66 containing imidazolium segments.

[0029] Preparation Example 2-2, modified nylon, was prepared according to the following operation: Under nitrogen protection, 5.0 mol adipic acid (730 g), 0.26 mol 4,5-imidazolium dicarboxylic acid (43 g), and 5.6 mol hexamethylenediamine (566 g) were added to a high-pressure polymerization reactor, along with 3.0 g phosphoric acid as a catalyst. The reactor was heated to 80-90°C with stirring and held for 30 minutes to allow the adipic acid, imidazolium dicarboxylic acid, and hexamethylenediamine to fully react and form a modified nylon salt aqueous solution. The temperature was then raised to 180°C and held at atmospheric pressure for 1.8 hours for pre-polymerization, during which the generated water was continuously drained and the reactor pressure was controlled to ≤0.3 MPa. Subsequently, the temperature was raised to 235°C, and the vacuum was gradually reduced to ≤150 Pa. The polymerization reaction continued for 2.0 hours until the melt viscosity stabilized. Heating was stopped, and nitrogen gas (0.2 MPa) was introduced to break the vacuum. The material was discharged, water-cooled and pelletized, and then vacuum-dried at 80°C for 8 hours to obtain modified nylon 66 containing imidazolium segments.

[0030] Preparation Example 2-3, modified nylon, was prepared according to the following operation: Under nitrogen protection, 5.0 mol adipic acid (730 g), 0.72 mol 4,5-imidazolium dicarboxylic acid (120 g), and 6.4 mol hexamethylenediamine (653 g) were added to a high-pressure polymerization reactor, along with 5.0 g phosphoric acid as a catalyst. The reactor was heated to 80-90 °C with stirring and held for 30 minutes to allow the adipic acid, imidazolium dicarboxylic acid, and hexamethylenediamine to fully react and form a modified nylon salt aqueous solution. The temperature was then raised to 180 °C and held at atmospheric pressure for 2.3 hours for pre-polymerization, during which the generated water was continuously drained and the reactor pressure was controlled to ≤0.3 MPa. Subsequently, the temperature was raised to 245 °C, and the vacuum was gradually reduced to ≤80 Pa. The polymerization reaction continued for 3.0 hours until the melt viscosity stabilized. Heating was stopped, and nitrogen gas (0.2 MPa) was introduced to break the vacuum. The material was discharged, water-cooled and pelletized, and then vacuum-dried at 90 °C for 6 hours to obtain modified nylon 66 containing imidazolium segments.

[0031] Preparation Examples 2-4, nylon resins, differ from Preparation Example 1 in that 4,5-imidazolium dicarboxylic acid is replaced with an equimolar amount of adipic acid.

[0032] Example Example 1: A angular double-wall corrugated power pipe is prepared according to the following steps: The inner wall material was weighed according to the formula: 10 kg of polypropylene (M800E, Shanghai Petrochemical), 1500 g of talc powder (average particle size 2 μm), and 200 g of calcium stearate lubricant. After mixing evenly, it was dried at 70℃ for 3 hours. The outer wall material was weighed according to the formula: 10 kg of polypropylene (M800E, Shanghai Petrochemical), 750 g of styrene-butadiene rubber (SBR 1500), 450 g of maleic anhydride-grafted polypropylene (CMG9801), 2000 g of modified carbon black (obtained in Preparation Example 1-1), 4 g of dicumyl peroxide (DCP, purity 98%), 200 g of calcium stearate, and 800 g of modified nylon (obtained in Preparation Example 2-1). g, after blending, is dried at 75℃ for 2.5 hours; the dried inner and outer layer materials are added to a twin-screw co-extrusion system, and under nitrogen micro-positive pressure protection, the temperatures of each zone are set as follows: feeding section 180℃, compression section 210℃, metering section 225℃, and die head 230℃. The concentric double-layer tube blank is formed by extrusion through the composite die head; the tube blank enters the angle corrugated forming machine (corrugation pitch 40 mm, corrugation height 12 mm), and is molded under the synergistic action of vacuum degree −0.06 MPa and internal pressure 0.035 MPa, and simultaneously sprayed with cooling water (water temperature 20℃) for shaping; thus, the angle-shaped electric double-wall corrugated pipe is obtained.

[0033] Example 2: A angular double-wall corrugated power pipe is prepared according to the following steps: The inner wall material was weighed according to the formula: 10 kg of polypropylene (M800E, Shanghai Petrochemical), 1000 g of talc powder (average particle size 2 μm), and 100 g of calcium stearate lubricant. After mixing evenly, it was dried at 70℃ for 3 hours. The outer wall material was weighed according to the formula: 10 kg of polypropylene (M800E, Shanghai Petrochemical), 500 g of styrene-butadiene rubber (SBR 1500), 300 g of maleic anhydride-grafted polypropylene (CMG9801), 1500 g of modified carbon black (obtained in Preparation Examples 1-2), 3 g of dicumyl peroxide (DCP, purity 98%), 100 g of calcium stearate, and 500 g of modified nylon (obtained in Preparation Example 2-2). g, after blending, is dried at 70℃ for 2.5 hours; the dried inner and outer layer materials are added to a twin-screw co-extrusion system, and under nitrogen micro-positive pressure protection, the temperatures of each zone are set as follows: feeding section 175℃, compression section 205℃, metering section 220℃, and die head 225℃. The concentric double-layer tube blank is formed by extrusion through the composite die head; the tube blank enters the angle corrugated forming machine (corrugation pitch 40 mm, corrugation height 12 mm), and is molded under the synergistic action of vacuum degree −0.05 MPa and internal pressure 0.03 MPa, and simultaneously sprayed with cooling water (water temperature 20℃) for shaping; thus, the angle-shaped electric double-wall corrugated pipe is obtained.

[0034] Example 3: A angular double-walled corrugated power pipe is prepared according to the following steps: The inner wall material was weighed according to the formula: 10 kg of polypropylene (M800E, Shanghai Petrochemical), 2000 g of talc powder (average particle size 2 μm), and 300 g of calcium stearate lubricant. After mixing evenly, it was dried at 80℃ for 3.5 hours. The outer wall material was weighed according to the formula: 10 kg of polypropylene (M800E, Shanghai Petrochemical), 1000 g of styrene-butadiene rubber (SBR 1500), 600 g of maleic anhydride-grafted polypropylene (CMG9801), 2500 g of modified carbon black (obtained in Preparation Examples 1-2), 5 g of dicumyl peroxide (DCP, purity 98%), 300 g of calcium stearate, and 1200 g of modified nylon (obtained in Preparation Example 2-2). g, after blending, is dried at 80℃ for 3 hours; the dried inner and outer layer materials are added to a twin-screw co-extrusion system, and under nitrogen micro-positive pressure protection, the temperatures of each zone are set as follows: feeding section 185℃, compression section 215℃, metering section 230℃, and die head 235℃. The concentric double-layer tube blank is formed by extrusion through the composite die head; the tube blank enters the angle corrugated forming machine (corrugation pitch 40 mm, corrugation height 12 mm), and is molded under the synergistic action of vacuum degree −0.07 MPa and internal pressure 0.04 MPa, and simultaneously sprayed with cooling water (water temperature 20℃) for shaping; thus, the angle-shaped electric double-wall corrugated pipe is obtained.

[0035] Example 4, an angled double-walled corrugated pipe for electric applications, differs from Example 1 in that an equal amount of the nylon resin used in Preparation Examples 2-4 is used to replace the modified nylon used in Preparation Example 2-1.

[0036] Example 5, an angled double-wall corrugated pipe for electric power, differs from Example 1 in that an equal amount of butyl rubber (Yanshan IIR-1751) is used to replace styrene-butadiene rubber (SBR 1500).

[0037] Comparative Example Comparative Example 1, an angled double-walled corrugated pipe for electric applications, differs from Example 1 in that the modified carbon black in Preparation Example 1-1 is replaced with an equal amount of 1-4 of modified carbon black.

[0038] Comparative Example 2, an angled double-walled corrugated pipe for electric power, differs from Example 1 in that the modified carbon black of Preparation Example 1-1 is replaced with an equal amount of the modified carbon black of Preparation Example 1-5.

[0039] Performance testing Experiment 1: Ring Stiffness Test Sample preparation: Six sample segments with a length of (300±20) mm were randomly cut from the conduits prepared in each embodiment and comparative example. Each sample must contain at least five complete corrugation cycles. The prepared samples were conditioned in a standard laboratory environment at (23±2)℃ and (50±10)% relative humidity for no less than 24 hours.

[0040] Test Method: The test shall be conducted according to GB / T 9647-2015 "Determination of Ring Stiffness of Thermoplastic Pipes" using a ring stiffness testing machine equipped with a parallel loading plate and an inner diameter measurement system. The specimen shall be placed vertically at the center of the lower platen of the testing machine. Pressure shall be applied to the specimen at a constant compression rate (causing a relative radial deformation of 3% ± 1% per minute). The ring stiffness value of a single specimen shall be recorded. The specimen shall be rotated approximately 120° and 240° relative to the initial loading position, and the above steps shall be repeated twice. The arithmetic mean of the three measurements shall be taken as the final ring stiffness result for this batch of conduits, rounded to two decimal places. Experiment 2: Impact Resistance Test Sample preparation: The required samples were cut from the catheters prepared in each example and comparative example, with a sample length of 200±10mm.

[0041] The test shall be conducted according to section 8.3.6 of DL / T 802.1-2023. The specimens shall be pretreated at 0±2℃ for at least 1 hour, and each specimen shall be impacted within 20 seconds after removal. Ten specimens shall be taken, and the hammer shall impact the peak of the impact wave from the top of the specimen once. The hammerhead spherical radius of curvature shall be 50 mm, the punch column diameter 90 mm, the hammer mass 3.0±0.01 kg, the impact height 1.2±0.01 m, and the total number of impacts 100. The test results shall be calculated according to the formula: "True Impact Rate (TIR value) = Total number of impact failures / Total number of impacts × 100%".

[0042] Table 1. Performance Test Results Example 1 13.8 2 Example 2 12.1 3 Example 3 14.7 2 Example 4 11.2 6 Example 5 11.7 4 Comparative Example 1 15.6 11 Comparative Example 2 16.9 14 Experimental data analysis: Compared to Example 1, Example 4, which replaced the imidazole-modified nylon with nylon 66 without imidazole segments, showed significantly worse performance in ring stiffness and total impact resistance (TIR), indicating that nylon containing imidazole segments has a positive effect on improving the rigidity and toughness of the pipe. This may be because the imidazole segments are crucial for constructing the metal phthalocyanine-polymer coordination network. Ordinary nylon cannot form axial coordination bonds with zinc phthalocyanine on the carbon black surface, resulting in only physical bonding at the filler-matrix interface. Pressure and impact energy cannot be conducted or dissipated through the coordination network, thus reducing rigidity and toughness. Example 5, which replaced styrene-butadiene rubber with butyl rubber, showed a slight decrease in impact resistance, indicating that the benzene ring structure in the rubber molecule has a positive effect on carbon black dispersion. This may be because butyl rubber has a saturated aliphatic hydrocarbon structure and lacks aromatic rings, preventing π-π interactions with the conjugated plane of the metal phthalocyanine, leading to decreased uniformity of modified carbon black dispersion, increased local stress concentration, and impaired impact performance.

[0043] Compared to Example 1, Comparative Example 1, which uses a physical adsorption method to load zinc phthalocyanine onto carbon black, shows a significant improvement in ring stiffness, but a more pronounced deterioration in impact resistance. This may be because the in-situ synthesized coating of the metal phthalocyanine layer is more effective at shielding the active sites of carbon black than physical adsorption. Furthermore, physically adsorbed zinc phthalocyanine is prone to detachment during high-temperature extrusion and has a poor barrier effect, failing to effectively block free radical attack on carbon black. This leads to graft crosslinking between carbon black and PP, resulting in excessively high material rigidity and increased brittleness. Comparative Example 2, which uses a silane coupling agent to modify carbon black, exhibits the worst impact resistance, but also shows a significant improvement in ring stiffness. This may be because silane modification also fails to effectively block free radical attack from silicon carbon black, leading to graft crosslinking between carbon black and PP. Simultaneously, it cannot participate in the construction of the coordination network, further degrading the overall performance.

[0044] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A type of angled double-wall corrugated electric pipe, characterized in that, The formulation of the inner wall of the corrugated pipe includes the following raw materials in parts by weight: 100 parts polypropylene, 10-20 parts filler, and 1-3 parts lubricant. The outer wall of the corrugated pipe is formulated with the following raw materials in parts by weight: 100 parts polypropylene, 5-10 parts unsaturated hydrocarbon elastomer, 3-6 parts maleic anhydride-grafted polyolefin, 15-25 parts modified carbon black, 0.03-0.05 parts free radical initiator, and 1-3 parts lubricant; the modified carbon black is coated with a metal phthalocyanine molecular layer; the preparation method of the modified carbon black is as follows: Carbon black was dispersed in an organic solvent at a concentration of 10–30 mg / mL, and then sonicated to obtain a suspension. A phthalonitrile precursor with a molar ratio of 4–7:1 is mixed with a metal salt and added to a suspension, such that the total mass ratio of the phthalonitrile precursor to the metal salt to the carbon black is 4–10:

1. The mixture is stirred and reacted at 170–230°C for 2–5 hours under an inert atmosphere. After the reaction is completed, the mixture is cooled, filtered, washed, and dried to obtain carbon black with a metal phthalocyanine molecular layer coated on its surface. The average particle size of the carbon black is 20–100 nm. The metal salt is a zinc salt hydrate or a copper salt hydrate.

2. The angled double-wall corrugated power pipe according to claim 1, characterized in that, The outer wall material also includes 5 to 12 parts of modified nylon, wherein the modified nylon molecule contains an imidazole segment.

3. The angled double-wall corrugated pipe for electric power according to claim 2, characterized in that, The modified nylon is obtained by polycondensation of adipic acid, 4,5-imidazolium dicarboxylic acid and hexamethylenediamine in a molar ratio of 1:0.05-0.15:1.1-1.

3.

4. The angled double-wall corrugated pipe for electric power according to claim 1, characterized in that, The unsaturated hydrocarbon elastomer is styrene-butadiene rubber.

Citation Information

Patent Citations

  • MPP corrugated cable conduit resistant to electromagnetic shielding and preparation method of MPP corrugated cable conduit

    CN118667263A

  • Laminated Tube

    JP6614402B1